Concentrations of Artificial Sweeteners and Their Ratios with Nutrients in Septic System Wastewater. Issue 3 (31st August 2017) - Snider, David M.; Roy, James W.; Robertson, William D.; Garda, Dorothy I.; Spoelstra, John
Abstract: This study reports the first comprehensive data set of characteristic concentrations of four artificial sweeteners: acesulfame (ACE), sucralose (SUC), saccharin (SAC), and cyclamate (CYC), and their ratios with nutrients, for untreated septic system wastewater. Samples were collected from the tanks of 19 different septic systems from across Ontario, Canada; these had a variety of usages, from single‐family cottages to multiple‐dwelling (campground or resort) facilities and had no additional treatment systems. The artificial sweetener concentrations and their relative proportions were highly variable in some cases, both temporally for several individual tanks and from site‐to‐site. Variability tended to be lower for multiple‐dwelling compared to single‐dwelling systems. This variability likely reflects differing use of artificial sweetener‐containing products. The median concentrations for the complete data set of all four artificial sweeteners (in a range of 10 to 60 μg/L) were of a similar order of magnitude, but slightly higher, than has generally been reported for wastewater treatment plant influent (though these vary substantially globally). Both SUC and ACE provided adequate positive linear relationships for dissolved nitrogen and phosphorus in the septic tanks, while a summation of ACE and SUC concentrations also gave a strong correlation. In contrast, CYC and SAC showed poor linear correlation with these nutrients. These reported ranges for artificial sweetener concentrations and ratios with nutrients may be used in future studies to estimate the contributions of nutrients or other wastewater constituents (e.g., pharmaceuticals, bacteria, and viruses) from domestic septic systems to groundwater, including water supply or irrigation wells, and nearby surface water bodies.